2019
DOI: 10.3389/fgene.2018.00680
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ancestral Differences and Reassessment of the Classification of Previously Reported Pathogenic Variants in Patients With Brugada Syndrome in the Genomic Era: A SADS-TW BrS Registry

Abstract: Brugada syndrome (BrS) is a heritable disease that results in sudden cardiac death. In the exome/genomic era, certain reported pathogenic variants in some genetic diseases have been reclassified as benign owing to their high frequency in some ancestries. In the present study, we comprehensively reassessed all previously reported pathogenic variants of BrS. We collected all pathogenic variants of BrS reported in the Human Gene Mutation Database and ClinVar throughout April 2017. We compared the minor allele fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…Electrophysiological analysis of M1875T in Nav1.5 showed disrupted fast inactivation, which is similar to a functional abnormality with our mutations . Furthermore, p.K1872N, which is located near the mutations in this study, in helix αV of EFL in Nav1.5, was reported as a pathogenic mutation of Brugada syndrome . This evidence strengthens the significance of EFL for Nav channel function.…”
Section: Discussionsupporting
confidence: 87%
“…Electrophysiological analysis of M1875T in Nav1.5 showed disrupted fast inactivation, which is similar to a functional abnormality with our mutations . Furthermore, p.K1872N, which is located near the mutations in this study, in helix αV of EFL in Nav1.5, was reported as a pathogenic mutation of Brugada syndrome . This evidence strengthens the significance of EFL for Nav channel function.…”
Section: Discussionsupporting
confidence: 87%
“…It has been suggested that post-translational modifications, such as a defect in the splicing process [93] or trafficking [94,95], or a modification in phosphorylation, methylation, or acetylation [96], could explain alterations in the function of the channel encoded by SCN5A in the absence of mutations in this gene itself. Also, the predicted phenotypic effect of a particular variant should take into consideration that ancestry can affect the pathogenicity of a particular variant [97]. Thus, there are several factors that can contribute to channel function, or dysfunction, other than mutations in the SCN5A gene itself that encodes for the Na V 1.5 protein.…”
Section: Sodium Channel Mutationsmentioning
confidence: 99%
“…Thus, periodic reclassification of rare variants is recommended before clinical translation; as of yet, there is no concrete timeframe for this process. Currently, only a few reports have addressed this novel challenge (Bennett et al 2019;Campuzano et al 2020a, b;Chen et al 2018;Denham et al 2018;Salfati et al 2019;VanDyke et al 2020) despite the impact reclassifications can have improving psychological outcomes and risk stratification while promoting personalized management (Macklin et al 2019;Tsai et al 2019). In this study, we updated data to reclassify rare variants associated with the most common ICC, classified 5 years ago following ACMG recommendations, and potential clinical impact.…”
Section: Introductionmentioning
confidence: 97%